Logo taboos: redesigning the visual identity of the Cyprus University of Technology - Zantides, Evripides (My University, 2017)
The Cyprus University of Technology was founded on December 2003 and welcomed its first students on September 2007. Since its establishment, the University has been using for its logo an icon of a fifth century Byzantine mosaic known as the goddess Ktisis (KTICIC), a personification symbolising the creation of the world (see figure 1). The specific image is exposed for public viewing at the ancient theatre of Curium in Limassol-Cyprus, and is arbitrarily photographed by a number of local companies and institutions as a symbol of their logo and brand strategy as well. Because of issues of copyrights and accessibility, in addition to serious problems of readability and adaptation in various applications, mediums, and sizes, the senate decided to proceed with a refinement, as well as ask for the option to design a new logo for the Cyprus University of Technology. That would differentiate it from the rest and diminish its current graphic design problems. Additionally, the whole idea would contribute to the re-branding actions that the University decided to proceed in 2017. As a consequence of this decision, a series of protests and arguments came into place, based on beliefs that such activities are too sacred to commence, and that changing the logo of the University should be prohibited. The aim of the current paper is to argue that the idea of changing the visual identity of a University should not be treated as a taboo, but as a decision that if executed professionally, could only work for its benefit. In doing so, the study seeks to present the art and design process that was undertaken for the development of a new logotype, and show the conceptualisation of its various design stages. Particularly, the presentation will build on the reasons that lead to a visual identity change, discuss current trends and aesthetics of University logos, analyse the design and semiotic parameters that should be considered when redefining logotypes, and argue the benefits of a new visual identity and long term branding. The design results show that the implementation of the new logo (see figure 2) has been widely embraced by a great number of academics, students, and the wider public, in spite of the taboo around the whole idea or the propagandistic actions that took place during its making.
Keywords: Logo; Cyprus University of Technology; Visual identity